Local constructions of vulnerability and resilience in the context of climate change. A comparison of Lübeck and Rostock. - Christmann, Gabriela B.; Balgar, Karsten; Mahlkow, Nicole (MDPI, 2014)
Climate change is globally defined as a "reality". This does not mean however that the way in which it is understood is the same all over the world. Rather, perceptions may differ at different places and times, even if physical and geographical conditions are similar. For the time being, this phenomenon has not been dealt with on a theoretical-conceptual level. The article will address this desiderate. Based on the approaches of social constructivism as well as actor-network theory, a theoretical concept will be suggested as a heuristic model for empirical analysis. By the examples of Lübeck and Rostock, two cities on Germany's Baltic coast, it will be shown that climate change related perceptions of vulnerability and resilience may build on physical-material aspects but that they are above all considerably interwoven with specific cultural and social patterns of interpretation. In the framework of the local discourse in Lübeck, it is the strong Hanseatic tradition which consumes the climate change issue, whereas in Rostock it is the problems and historical breaks of a transformation society which shape the way of viewing climate change.
Keywords: Hochwasserschutz; Gemeinde; Großstadt; Risikoanalyse; Resilienz; Vulnerabilität; Klimawandel